2019
DOI: 10.3390/ijms20246365
|View full text |Cite
|
Sign up to set email alerts
|

“Salicylic Acid Mutant Collection” as a Tool to Explore the Role of Salicylic Acid in Regulation of Plant Growth under a Changing Environment

Abstract: The phytohormone salicylic acid (SA) has a crucial role in plant physiology. Its role is best described in the context of plant response to pathogen attack. During infection, SA is rapidly accumulated throughout the green tissues and is important for both local and systemic defences. However, some genetic/metabolic variations can also result in SA overaccumulation in plants, even in basal conditions. To date, more than forty Arabidopsis thaliana mutants have been described as having enhanced endogenous SA leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…The mutant collection presented by Pluhařová and co-workers provides a very valuable tool to better understand the mechanisms underlying trade-offs between growth and defence in plants. The authors present a novel research study, providing new insights clarifying a link between SA and plant behaviour under environmental stresses [24]. They showed a negative correlation between the SA content and the rosette size, but not the root growth.…”
Section: What Are the New Directions?mentioning
confidence: 94%
See 1 more Smart Citation
“…The mutant collection presented by Pluhařová and co-workers provides a very valuable tool to better understand the mechanisms underlying trade-offs between growth and defence in plants. The authors present a novel research study, providing new insights clarifying a link between SA and plant behaviour under environmental stresses [24]. They showed a negative correlation between the SA content and the rosette size, but not the root growth.…”
Section: What Are the New Directions?mentioning
confidence: 94%
“…These papers cover a wide range of aspects of SA-related mechanisms. They include a "classical" demonstration of the importance of SA in biotic stress [23] and the importance of the use of various mutants related to SA signalling [24,25], as well as focus on the crosstalk with other stress-related compounds [25,26]. There are also works investigating the effects of environmental factors on the SA-related signalling [26,27], and on the role of different SA analogue compounds [28].…”
Section: What Are the New Directions?mentioning
confidence: 99%
“…A complex network of regulatory pathways fine tunes the timing of the plant senescence in response to both external and internal clues, such as plant pathogen, nutrient starvation, and phytohormones, including abscisic acid, jasmonic acid, ethylene, and SA. For instance, SA levels in leaves participates to the natural senescence by regulating the expression of genes that are also modified by abiotic stresses (Morris et al, 2000;Lim et al, 2007). Following the N percentage in leaves and the N remobilization from the leaves to the seeds, we provided evidence that ACD6 acts on N mobilization during leaf senescence (Figures 4A,C).…”
Section: Acd6 Modulates Finely the Nitrogen Remobilization Efficiencymentioning
confidence: 74%
“…Little is known about the molecular function of ACD6 protein ( Lu et al, 2005 ). Nevertheless, it has been demonstrated that the ACD6 protein plays a major role in plant response to biotic and abiotic stresses through the SA signaling pathway ( Rate et al, 1999 ; Todesco et al, 2014 ; Pluhařová et al, 2019 ). During pathogen infection, the rise in SA levels in leaves triggers the cell death program and leaf necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many plants with altered immune pathways exhibit strong pleiotropic phenotypes, including growth retardation (Rate et al , 1999; Yi & Richards, 2008). The behaviour of those plants is thus significantly affected by hormonal misregulation, especially SA increase (Pluharova et al , 2019). The crossing of those mutants will bring new biases that need to be carefully interpreted.…”
Section: Figmentioning
confidence: 99%